Prices, Wages and Inflation after the Euro - What Europeans Shoud or Should not Expect - Giancarlo Corsetti; John Flemming; Seppo Honkapohja; Willi Leibfritz; Gilles Saint-Paul; Hans-Werner Sinn; Xavier Vives (CESifo Forum, 2002)
This chapter addresses questions about the effect of the introduction of the euro on price differentials across the Union and also on the cost of capital in its member countries, which may account for capital flows from the slow growing centre to the more buoyant peripheral states. Nominal interest rates on government securities have converged virtually completely with the announcement and introduction of the euro, indicating that risk premia resulting from uncertain exchange rates and other causes have disappeared. As these premia are generally believed to have been higher in the peripheral states, these should now be benefiting from a reallocation of capital in their favour. As a result, labour productivity and prices of goods that are not traded internationally can be expected to rise faster than would have been the case without the euro. A sizeable inflation differential among the Euro countries is a natural aspect of the real convergence process that has been brought about by European integration in general and by the euro in particular. So, while high inflation at time of booms in domestic demand may be a useful way to contain domestic imbalances, prices and wages then need to come down after the boom is over. The adoption of policies promoting wage and price flexibility is a key step in the future of the Euro area.
Keywords: 330